ANALISIS SWOT DALAM PERENCANAAN STRATEGIS SEKOLAH UNTUK PENINGKATAN MUTU PENDIDIKAN - Sormin, Eunike Gracia; Budianto, Agum; Nabila, Farah; Siregar, Husnah; Reni, Monica Intan; Putri, Sasri Agustina; Utami, Nadia Dwi (Universitas Negeri Medan, 2025)
This study analyzes the application of SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) as a strategic instrument in planning quality improvement in elementary schools. The main focus of this study is how SWOT analysis can help schools formulate adaptive, collaborative, and sustainability-oriented policies amid the challenges of globalization and digital transformation. This analytical approach not only serves as a tool for identifying the internal and external conditions of schools, but also as a reflective mechanism to strengthen the participation of all stakeholders, including principals, teachers, parents, and the community, in creating a culture of sustainable quality. The results of the study show that the application of SWOT can improve the effectiveness of school strategic planning through the formulation of policies based on data and real needs, strengthen adaptive capabilities to policy changes, and encourage more visionary and measurable decision-making. Critically, this study emphasizes that SWOT analysis is not merely an administrative procedure, but part of the transformation of educational management towards a reflective, participatory, and quality-oriented system. Through the optimal utilization of internal strengths and external opportunities, elementary schools can become learning institutions that are resilient, innovative, and relevant to the needs of the 21st century.